Rethinking Machiavelli’s The Prince: Humanist Critique and the Ethics of Objective Inquiry - Brdar, Milan (Napredak, 2025)
This paper demonstrates that a proper understanding of Machiavelli’s The Prince requires a careful reconstruction of the historical and cultural context of the Renaissance at the turn of the fifteenth to the sixteenth century. Particular attention is given to the humanists’ teaching on the virtuous man (vir virtutis) and the “mirror for princes” genre that emerged from it. Within this framework, the persistent humanist critique of Machiavelli – one that continued to exert influence well into the twentieth century – can be fully comprehended. In contrast, the interpretation advanced here contends that Machiavelli was the first to introduce a principle of methodological objectivity, later described as the value-neutral inquiry. By adopting this stance, Machiavelli can be regarded as a pioneer of political science: without the methodological foundation he established, the discipline itself could not have developed. Through adherence to this principle, he was able to present an objective account of political reality and to make it publicly intelligible, demonstrating remarkable intellectual courage. In light of this achievement, Machiavelli deserves rehabilitation from the long-standing accusations and recognition as an impartial investigator of the nature of politics— a role that humanist criticism has never been able acknowledge.